1998
DOI: 10.1046/j.1365-2958.1998.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein kinase that controls carbon catabolite repression in bacteria

Abstract: SummaryHPr(Ser) kinase is the sensor in a multicomponent phosphorelay system that controls catabolite repression, sugar transport and carbon metabolism in Grampositive bacteria. Unlike most other protein kinases, it recognizes the tertiary structure in its target protein, HPr, a phosphocarrier protein of the bacterial phosphotransferase system and a transcriptional cofactor controlling the phenomenon of catabolite repression. We have identified the gene (ptsK ) encoding this serine/threonine protein kinase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
229
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(242 citation statements)
references
References 71 publications
9
229
1
3
Order By: Relevance
“…The role of FBP is to stimulate phosphorylation of HPr at Ser-46, which is catalyzed by HPr kinase/phosphatase (HPrK/ P), as was verified later. [71][72][73][74] (HPr is a histidinecontaining protein involved in carbohydrate transport via the phosphoenolpyruvate:sugar phosphotransferase system.) 75) Thus HPr-mutants (ptsH1) are partially or completely relieved from CCR of several catabolic genes.…”
Section: Elucidation Of the Signal Transduction Mechanism Underlying mentioning
confidence: 99%
“…The role of FBP is to stimulate phosphorylation of HPr at Ser-46, which is catalyzed by HPr kinase/phosphatase (HPrK/ P), as was verified later. [71][72][73][74] (HPr is a histidinecontaining protein involved in carbohydrate transport via the phosphoenolpyruvate:sugar phosphotransferase system.) 75) Thus HPr-mutants (ptsH1) are partially or completely relieved from CCR of several catabolic genes.…”
Section: Elucidation Of the Signal Transduction Mechanism Underlying mentioning
confidence: 99%
“…A HPr-like protein, Crh (for catabolite repression HPr), was discovered in B. subtilis, and it was shown to be involved as well in carbon catabolite repression by a similar phosphorylation of its Ser-46 residue (4). The long search for the enzyme responsible for HPr or Crh phosphorylation ended lately thanks to the B. subtilis sequencing program, with the identification of its encoding hprK gene (5,6). Genomic programs have since shown that this gene is present not only in most Gram-positive bacteria but also in some pathogenic Gram-negative species.…”
mentioning
confidence: 99%
“…The two dissimilar i HPRR controls the transcription-enhancing phosphorylation reactions are mutually ant-activity of its effector domains. Accordingly, agonistic and they exert opposing effects on i Enzyme I and HPRR may be analogous to transcription (12,13,15). These phosphory-sensor kinases and response regulators, lation-dependent regulatory mechanisms are f respectively, of classical two-component the only currently documented cases in which the PTS functions directly in transcriptional f HPRR (667 aa) is encoded in a monociscontrol.…”
Section: A Hybrid Response Regulator Possessing a Pep-dependent Phospmentioning
confidence: 99%